2012
DOI: 10.1038/aps.2012.27
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of endothelial NOS contributes to simvastatin protection against myocardial no-reflow and infarction in reperfused swine hearts: partially via the PKA signaling pathway

Abstract: Aim: The cholesterol-lowering drugs statins could enhance the activities of endothelial nitric oxide synthase (eNOS) and protect myocardium during ischemia and reperfusion. The aim of this study was to examine whether protein kinase A (PKA) was involved in statinmediated eNOS phosphorylation and cardioprotection. Methods: 6-Month-old Chinese minipigs (20-30 kg) underwent a 1.5-h occlusion and 3-h reperfusion of the left anterior descending coronary artery (LAD). In the sham group, the LAD was encircled by a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 38 publications
1
12
0
3
Order By: Relevance
“…NO is a unique, endogenous regulatory molecule involved in various physiological processes. NO exerts some beneficial effects during myocardial reperfusion, including regulation of myocardial contractility, as well as effects on sarcolemmal and mitochondrial K ATP channel opening, antioxidant effects, and oxygen free radical production [23,24]. Although myocardial I/R may impair NO release, isoflurane exposure has been found to stimulate vascular endothelial cells to produce more NO in the ischemic-reperfused myocardium [16].…”
Section: Discussionmentioning
confidence: 99%
“…NO is a unique, endogenous regulatory molecule involved in various physiological processes. NO exerts some beneficial effects during myocardial reperfusion, including regulation of myocardial contractility, as well as effects on sarcolemmal and mitochondrial K ATP channel opening, antioxidant effects, and oxygen free radical production [23,24]. Although myocardial I/R may impair NO release, isoflurane exposure has been found to stimulate vascular endothelial cells to produce more NO in the ischemic-reperfused myocardium [16].…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological preconditioning(10 groups, n = 8 each): doses based on clinical usage in acute coronary syndrome and previous animal studies, with the following medicines intragastrically (i.g.) administered 1-h before LAD ligation: TXL(50 mg/kg, Yiling Co., Ltd., China)[ 4 ], valsartan(2 mg/kg, Novartis Co., Ltd., USA), rosuvastatin (4 mg/kg, AstraZeneca Co., Ltd., China), simvastatin (2 mg/kg, Merck Co., Ltd., USA) [ 24 , 25 ] and carvedilol (1 mg/kg, Roche Co., Ltd., Switzerland). Tirofiban (Yuanda Co., Ltd., China) was given as a 15 μg/kg intravenous (i.v.)…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we and others have shown that the cholesterol lowering drug statins can improve the ability of cardiovascular stem cells to resist inflammation [25] and repair and regenerate the heart damaged by ischemia or infarction [22,23,38,47]. Statins selectively inhibit 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase, a rate-limiting enzyme catalyzing the conversion of HMG-CoA to mevalonic acid and thereby attenuate endogenous biosynthesis of cholesterol.…”
Section: Introductionmentioning
confidence: 99%